FROM THE CHARACTER TO THE STYLE OF DALAT PEOPLE: THEORETICAL APPROACH AND FRAMEWORK OF CULTURAL ANTHROPOLOGY - Nguyễn Văn Tiệp (Tạp chí Khoa học Đại học Đà Lạt)
Research on national and regional identity, characteristics, and lifestyle has been receiving increasing attention from scholars in the context of modernization and global integration. From the perspective of American psychological anthropology, this paper presents research trends from cultural and psychological anthropology to suggest an understanding about national characteristics and to build a theoretical framework on the style of Dalat’s people.